Bacterial community profile of three Ethiopian hot springs based on 16S rRNA gene nanopore sequencing - Guta, Meseret; Van Eenooghe, Bodine; Bacha, Ketema; Cools, Piet (Scientific reports, 2025)
Ethiopia harbors a number of hot springs not yet well explored or studied using a metagenomic approach to reveal their bacterial diversity. Understanding the bacterial diversity of these ecosystems is valuable for uncovering their ecological roles and potential for biotechnological applications. The aim of this study was, therefore, to perform the first full-length 16S rRNA gene nanopore sequencing on the three Ethiopian hot springs, namely Shalla, Woliso and Wondo Genet. The bacterial community composition of the three hot springs, whose temperatures ranged from 45 to 96 °C, was effectively assessed using the ONT MinION sequencer. It was found that Shalla hot spring had the highest species richness and accounted for 323 species, followed by 116 species from Woliso and 54 species from Wondo Genet hot springs. Pseudomonadota and Bacillota were the most dominant phyla recovered from the three hot springs, whereas Acinetobacter and Paracoccus were the most abundant bacterial genera. The most abundant species were Alkalihalobacterium elongatum from Shalla hot spring, and Acinetobacter junii and Acinetobacter johnsonii from Wondo Genet hot spring. Our study provided the first insight into the bacterial diversity of three Ethiopian hot springs and may serve as a basis for further functional analysis of these hot springs.